Star Formation Quenching in Quasar Host Galaxies - Carniani, Stefano (Frontiers in Astronomy and Space Sciences, 2017)
Galaxy evolution is likely to be shaped by negative feedback from active galactic nuclei (AGN). In the whole range of redshifts and luminosities studied so far, galaxies hosting an AGN frequently show fast and extended outflows consisting in both ionised and molecular gas. Such outflows could potentially quench the start formation within the host galaxy, but a clear evidence of negative feedback in action is still missing. Hereby I will analyse integral-field spectroscopic data for six quasars at z ∼2.4 obtained with SINFONI in the H- and K-band. All the quasars show [OIII]λ5007 line detection of fast, extended outflows. Also, the high signal-to-noise SINFONI observations allow the identification of faint narrow Hα emission (FWHM < 500 km/s), which is spatially extended and associated with star formation in the host galaxy. On paper fast outflows are spatially anti-correlated with star-formation powered emission, i.e. star formation is suppressed in the area affected by the outflow. Nonetheless as narrow, spatially-extended Hα emission, indicating star formation rates of at least 50 - 100 M⊙/yr, has been detected, either AGN feedback is not affecting the whole host galaxy, or star formation is completely quenched only by several feedback episodes. On the other hand, a positive feedback scenario, supported by narrow emission in Hα extending along the edges of the outflow cone, suggests that galaxy-wide outflows could also have a twofold role in the evolution of the host galaxy. Finally, I will present CO(3-2) ALMA data for three out of the six QSOs observed with SINFONI. Flux maps obtained for the CO(3-2) transition suggest that molecular gas within the host galaxy is swept away by fast winds. A negative-feedback scenario is supported by the inferred molecular gas mass in all three objects, which is significantly below what observed in non-active main-sequence galaxies at high-z.